Soil and water conservation practice effects on soil physicochemical properties and crop yield in Ethiopia: review and synthesis - Jiru, Endale Bekele; Wegari, Habtamu Temesgen (Ecological processes, 2022)
Background Land degradation is an urgent agenda that requires great effort and resources to ameliorate. It worsens soil components through disrupting ecological functions and threatens agriculture production. To overcome it, different soil and water conservation (SWC) practices have been undertaken in numerous parts of Ethiopia. This paper aims to review the effects of SWC practices on soil physicochemical properties and crop yield. Data were collected from secondary sources via a computer library using various databases based on developed criteria. The collected data were organized, categorized, and analyzed through descriptive statistics. The mean difference of selected soil physicochemical properties obtained from treated and untreated farmland was tested using paired t -test. Factors influencing crop yield on treated farmland were determined by a multiple linear regression model. Results SWC practices influenced the soil physicochemical properties and crop yield either positively or negatively. The mean values of available phosphorus (10.6 ppm, 8.7 ppm), total nitrogen (0.5%, 0.4%), soil pH (6.0%, 5.8%), soil organic matter (4.4%, 3.8%), and soil organic carbon (2.2%, 1.8%) were on treated and untreated farmland under physical SWC practices, respectively. Similarly, the mean values of these variables were higher on treated farmland than untreated farmland under both biological and integrated SWC practices. The mean value of bulk density was higher on untreated farmland than treated one and statistically significant under all SWC practices. Fanya juu and stone-faced soil bund constantly increased crop yield, whereas soil bund and stone bund did not. Conclusion Proper implementation of SWC technologies through integrating physical and biological measures will boost the effectiveness of the practice in restoring soil physicochemical properties and improving crop yield. Meanwhile, government due attention paid for land resources management in Ethiopia, whereby the annual SWC and tree planting campaign underwent for a couple of decades, entails further scientific support for its efficacy.